228 GENDER DISPARITIES IN DIAGNOSING OSTEOPOROSIS. (18th November 2021) - Morrison, L; Fernandes, L; Lyons, D
Abstract: Background: It is estimated that up to 300, 000 people in Ireland have osteoporosis, however it is a disease most commonly associated with women. Women aged over 50 years have a four times greater rate of osteoporosis and are twice as likely to have osteopenia as men. 1 However the recognition and treatment of osteoporosis in men cannot be forgotten. The Irish Hip Fracture Database National Report 2019 showed that 31% of 3, 701 hip fractures that year were in males. Hip fractures have been shown to result in higher overall mortality in men than in women. 2 Methods: A retrospective observational study was carried out by analysing the reports of all dual-energy X-ray absorptiometry (DEXA) scans performed in a large university teaching hospital from January 1998 to August 2021, collecting data on gender, age, bone mineral density and osteoporosis risk factors. Results: A total of 39, 611 patients having their first DEXA scan in our hospital were included. 85.2% were female and 14.8% male. In all patients over 75 years, only 12.9% of all patients getting a first DEXA scan were male. Of all women who had DEXA scans, 29.1% were diagnosed with osteoporosis and 38.4% with osteopenia and in men 16.6% osteoporosis and 40.7% osteopenia. Conclusion: Our results highlight that men have DEXA scans performed much less frequently than women. This is seen in all age groups, especially in patients over 75 years old. As in women, the prevalence of osteoporosis in men increases with age. This study demonstrates the importance of evaluating for and treating osteoporosis in men as well as women, as fragility fractures can cause significant mortality and morbidity in both genders. References: 1. Alswat KA. Gender Disparities in Osteoporosis. J Clin Med Res .2017;9(5):382–387. doi: 10.14740/jocmr2970w . 2. Kanis JA et al. The components of excess mortality after hip fracture. Bone .2003;32(5):468–473.